Os recursos de tecnologia assistiva nas bibliotecas universitárias federais brasileiras: uma abordagem para as pessoas com deficiências visuais - Alejandro de Campos Pinheiro (2021)
This dissertation presents a descriptive research with a qualitative approach, with the objective of investigating in the libraries of Brazilian federal institutes and universities, the actions related to the Assistive Technology area that are being carried out, with an approach directed to people with visual impairments to satisfy your information needs. The increasing participation of people with visual impairments in different environments and with emphasis on access to higher education has impacted the forms of care, products and services offered by university libraries. University libraries need to assist these students in order to make the desired information accessible, regardless of the medium on which it is stored. For people with visual impairments, Assistive Technology resources become alternatives to access information, which is registered in books, periodicals and other documentary supports. The object of study falls primarily on Assistive Technology resources in Brazilian federal university libraries for people with visual impairments. The methodology used was bibliographic and documentary research, which includes the websites and documents published by the libraries of federal institutes and universities and the publication of databases and annals of events in the area of Library Science and Information Science, which address studies of cases on the use of Assistive Technology resources in university libraries and inclusive Brazilian federal legislation 883 university library sites were surveyed, in which 83 sites reported the presence of Assistive Technology resources. It is concluded that the majority of university libraries surveyed do not have or did not report the existence of Assistive Technology resources and, consequently, do not meet the requirements of inclusive legislation, impairing access to information for people with visual impairments. The need to raise public institutions' awareness of accessibility is understood, which includes university libraries, so that inclusive legislation is complied with, the implantation of Assistive Technology resources and the awareness and empathy of people and professionals, such as the librarian, to build an inclusive society.